Evaluation of water permeability in compacted sand-bentonite liners from landfill using planning and factorial analysis - Silva, Thiago Fernandes da; Lyra, Marcus Vinícius Melo de; Silva, Isaac Fernandes da; Paiva, William de; Melo, Marcio Camargo de; Monteiro, Veruschka Escarião Dessoles (Journal of Environmental Engineering and Landscape Management, 2024)
Compacted Clay Liners (CCL) are designed to prevent environmental contamination in landfills. These layers are designed with low permeability soils, which are difficult to obtain. To this end, bentonite can be added. The objective of this work is to evaluate the reliability of factor analysis on the hydraulic performance of sand-bentonite mixtures. Two types of designs were used, with the variables controlled: compaction energy (CE), water content (U) and percentage of bentonite (B). Experimental layers were made to obtain water permeability (kw). The results showed that CE and B are, respectively, the factors that most influence permeability. The application of adequate energy promotes better accommodation of bentonite soil particles in the voids in the sand, which, when moistened, undergo an expansion process, reducing the voids in the layer. All of these parameters can be optimized by using a curvature design to obtain kW. Therefore, knowledge of CCL kw is essential to ensure the safety of the local environmental environment.